Violence Against Latina Immigrants : Citizenship, Inequality, and Community - Villalon, Roberta; Villalon, Roberta (Book collections on Project MUSE., 2010)
Caught between violent partners and the bureaucratic complications of the US Immigration system, many immigrant women are particularly vulnerable to abuse. For two years, Roberta Villalón volunteered at a nonprofit group that offers free legal services to mostly undocumented immigrants who had been victims of abuse. Her innovative study of Latina survivors of domestic violence explores the complexities at the intersection of immigration, citizenship, and violence, and shows how inequality is perpetuated even through the well-intentioned delivery of vital services. Through archival research, participant observation, and personal interviews, Violence Against Latina Immigrants provides insight into the many obstacles faced by battered immigrant women of color, bringing their stories and voices to the fore. Ultimately, Villalón proposes an active policy advocacy agenda and suggests possible changes to gender violence-based immigration laws, revealing the complexities of the lives of Latina immigrants as they confront issues of citizenship, gender violence, and social inequalities.